Association Between Personality Types with Emotional Intelligence among First Grade Medical Students - Setiani, Innaya Ayu; Budiarso, Linda S. (Jambura Medical and Health Science Journal, 2025)
Introduction: Medical students are expected to possess various competencies and strong clinical skills to become competent and professional doctors. These demands require not only intellectual ability but also high emotional intelligence, which supports mental resilience, positive thinking, and social adaptability. Emotional intelligence is influenced by several internal factors, including personality type, commonly categorized as extroverted or introverted. The purpose of this study was to examine the relationship between extrovert and introvert personality types with the level of emotional intelligence in students of the Faculty of Medicine, Tarumanagara University, class of 2024.Method: This study employed an observational analytic design with a cross-sectional approach. A total of 194 medical students from the Faculty of Medicine, Tarumanagara University, Class of 2024, were selected using a simple random sampling technique. Data were collected using the Eysenck Personality Inventory (EPI) to assess personality types and the Assessing Emotional Scale (AES) to measure emotional intelligence. Data analysis was conducted using the Chi-Square test.Results: 57.7% of respondents were extroverts, while 43.3% were introverts. In terms of emotional intelligence, the majority (69.1%) were in the high category. The Chi-Square test showed a P-value of 0.000 (P0.05), indicating a statistically significant relationship between personality type and emotional intelligence.Conclusion: There is a significant relationship between personality type and the level of emotional intelligence among medical students. Extroverted students tend to have higher emotional intelligence, suggesting that personality traits may influence students’ emotional adaptability and resilience throughout their education. Keywords: Emotional intelligence, medical students, personality type